Study of the Electromagnetic Field Radiated From the Cell Phone Towers within Kathmandu Valley - Parajuli, Prakash; Panday, Jagat Prasad; Koirala, Rajendra Prasad; Shah, Buddha Ram (International Journal of Applied Sciences and Biotechnology, 2015)
With the increase in the use of the mobile phone, widely used wireless technology, people are highly conscious regarding the deleterious effects of the RF signals. To account this consciousness, this research work deals with the assessment of the radiation level near mobile Base Station Towers (BSTs) of Kathmandu valley with the analysis of the observed values in reference to the National and International guidelines and radiation norms adopted in different countries. “Tenmars, TM-196” and GPS map60Csx were employed for the measurement. It is found that the maximum value of the Power density in Kathmandu valley is 0.003602 W/m2 at Maximum Peak Point (MPP) near BST of New Baneshwor area, characterized by high traffic (Vicinity population) and all services across the BSTs and the minimum average radiation level far away from the BSTs (Off tower region) with access of the cellular network has 0.00000206 W/m2 Power density near Lele area, Lalitpur, which is far less than the Power density near the BSTs. It is found that all observed sites are within the standards of the Nepal Telecommunication Authority (NTA) in terms of the amount of EMFs that the base station is radiating. Power density highly depends on vicinity population and moderately depends on services across the BSTs. Also the BSTs are constructed haphazardly near School and Colleges, Hospitals etc. Int J Appl Sci Biotechnol, Vol 3(2): 179-187 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12297